Konseling Online: Sebuah Pendekatan Teknologi Dalam Pelayanan Konseling - Zadrian Ardi; Frischa Meivilona Yendi; Ifdil Ifdil (Jurnal Konseling dan Pendidikan, 2013)
Technological developments in recent decades have brought a positive impact for human activities. Various applications of technology that grows along with its case bore a lot of ease and problem solving. Counseling as one of efforts to develop an independent human being also requires varied approaches in the performance of its services. One of such approach is counseling online. Various forms and types of service in counseling can be applied by utilizing internet technology, such as Email, Chat Program, Videoconferencing Program dan Webcam. The development of online counseling approach it self in recent years showed significant increases and gets serious attention among professionals. In addition, the application of counseling online also carries a variety of positive impact to the creation of effective-daily-living conditions.